PENGARUH LABEL HALAL TERHADAP PILIHAN KONSUMEN GERAI INDOMART PANUMBANGAN KABUPATEN CIAMIS - Lilis D Hadaliah; Sri Maryani (Prodi Hukum Ekonomi Syariah (Muamalah), 2020)
This research aims to analyse the practice of halal labels as well as the process of consumer choice when choosing Halal products at Indomart Panumbangan. The data used in the study is primary data and secondary data. Primary Data is obtained directly from the survey dissemination to the research respondent. Secondary data is derived from literature, journals, or data related to research purposes. The population in this study is the consumer of Indomart Panumbangan, a sampling technique is a simple random sampling, a sampling of 50 people. Methods for collecting data using questionnaire or poll. The data analysis techniques in this study are validity and reliability tests, simple linear regression analyses as well as linear coefficient (R) analyses and determinations (R2). The results of the study showed the halal Label on each packaged food product offered at Indomart Panumbangan 90% of the official halal Label, the rest of which are labeled halal but not in accordance with the provisions of LPPOM MUI. The selection process on products labeled halal, consumers influenced cultural factors. From a variable X R2 test (Halal label) it affects 29.8% against Y (consumer choice). From simultaneous test results and variable X partial tests significantly affect the consumer's preference (Y).